Retirement Behaviour of Dutch Elderly Households: Diversity in Retirement Patterns across Different Household Types - Mauro Mastrogiacomo; Rob Alessie; Maarten Lindeboom (Tinbergen Institute, 2002)
This paper aims to assess the relative importance of differences in behaviouralresponses to financial incentives in explaining the observed variation in retirement behaviour across different types of households. We specify and estimate models for singles and married couples and estimate these on data from the Dutch Socio-Economic Panel. Model estimates are used to decompose the observed differences in retirement trends of the different demographic subgroups into differences in preferences and differences in theavailability and generosity of the retirement options.
Keywords: J26; 330; optimal stopping; household retirement; Altersgrenze; Ökonomischer Anreiz; Schätzung; Niederlande